2022
DOI: 10.1073/pnas.2123338119
|View full text |Cite
|
Sign up to set email alerts
|

5-methylcytosine (m 5 C) RNA modification controls the innate immune response to virus infection by regulating type I interferons

Abstract: 5-methylcytosine (m 5 C) is one of the most prevalent modifications of RNA, playing important roles in RNA metabolism, nuclear export, and translation. However, the potential role of RNA m 5 C methylation in innate immunity remains elusive. Here, we show that depletion of NSUN2, an m 5 C methyltransferase, significantly inhibits the replication and gene expression of a wide range of RNA and DNA viruses. Notably, we found that this antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…By conjoint analysis of the epitranscriptomic profile and expression profile, we identified 143 ‘hyper-up’, 4 ‘hyper-down’, 81 ‘hypo-up’, and 6 ‘hypo-down’ lncRNAs. GO analysis highlighted the enrichment of target genes of DM and DE lncRNAs in nucleosome assembly, and regulation of type I interferon production pathway which is consistent with the recent report of the involvement of m 5 C methylation in the regulation of lncRNAs expression and type I interferon production [ 15 ]. KEGG pathway analyses revealed that these DM and DE lncRNAs were predominantly associated with pathogen recognition and pathogenesis pathways.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…By conjoint analysis of the epitranscriptomic profile and expression profile, we identified 143 ‘hyper-up’, 4 ‘hyper-down’, 81 ‘hypo-up’, and 6 ‘hypo-down’ lncRNAs. GO analysis highlighted the enrichment of target genes of DM and DE lncRNAs in nucleosome assembly, and regulation of type I interferon production pathway which is consistent with the recent report of the involvement of m 5 C methylation in the regulation of lncRNAs expression and type I interferon production [ 15 ]. KEGG pathway analyses revealed that these DM and DE lncRNAs were predominantly associated with pathogen recognition and pathogenesis pathways.…”
Section: Discussionsupporting
confidence: 89%
“…2 A). To evaluate the reliability of our data, LncRNA RPPH1, VTRNA1-1 and SCARNA2, which have been reported harboring m 5 C modification sites [ 15 , 34 ], were examined and the m 5 C peaks detected in our data were visualized by IGV (Supplementary Fig. 2A in Additional file 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, firstly, we revealed a novel mechanism by which the m 5 C machinery functions in innate immune responses via the methylation of IRF3 mRNA to negatively regulate type I interferon responses [ 51 ], indicating that the m 5 C and m 6 A machineries may have different specificities with respect to regulating multiple signalling molecules involved in antiviral innate immune responses. Recently on October 2022, Zhang et al also reported that depletion of NSUN2 enhanced type I interferon response and inhibited virus replication, which is dependent on RIG-I but not MDA5 [ 52 ]. But the mechanism they reported is different from what we found, which implies the important function of m 5 C modification in innate immune regulation during various viral infections.…”
Section: Discussionmentioning
confidence: 99%